Corticosterone: effects on feather quality and deposition into feathers. Issue 2 (2nd February 2015) - Jenni‐Eiermann, Susanne; Helfenstein, Fabrice; Vallat, Armelle; Glauser, Gaétan; Jenni, Lukas
Summary: The concentration of the glucocorticoid hormone corticosterone (CORT) is increasingly used in ecology and conservation biology as an integrated measure of the historical record of an individual's hypothalamo–pituitary–adrenal (HPA) activity during feather growth. However, where and how CORT is incorporated in feathers is incompletely known. We therefore examined whether CORT is reliably measured with an enzyme immunoassay, where CORT is incorporated in the feather and where it affects feather quality, and whether CORT incorporation is related to plasma CORT levels, feather growth rate and melanin pigmentation. During the regrowth of plucked tail feathers, we injected pigeons with tritium‐labelled CORT, and implanted a CORT‐releasing pellet to increase plasma CORT concentration for about 3 days. In feather segments, we measured labelled CORT (DPM3H ) and we quantified CORT with an enzyme immunoassay EIA (CORTEIA ) and double‐checked the results with ultra‐high performance liquid chromatography–tandem mass spectrometry (LCMS) (CORTMS ). Administered CORT affected feather structure and colour at the very base of the feather (epidermal collar, ramogenic zone) and reduced growth rate. In contrast, incorporation of CORT into the feather happened mainly in the blood quill, as shown with all three methods (DPM3H, CORTEIA and CORTMS ). Incorporation of CORT into feathers was only roughly proportional to plasma concentration, proportional to feather growth rate and increased with melanin pigmentation. Measuring CORT in feather is a way to reveal past events of increased stress during feather growth in birds.